2022
DOI: 10.1101/2022.09.20.508761
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Critical role of growth medium for detecting drug interactions in Gram-negative bacteria that model in vivo responses

Abstract: The rise in infections caused by multidrug-resistant (MDR) bacteria has necessitated a variety of clinical approaches, including the use of antibiotic combinations. Antibiotic susceptibility is affected in part by the growth state of bacteria within various tissues. Here we tested the hypothesis that drug-drug interactions vary in different media, and hence, using a medium that reflects tissue environments will better predict in vivo outcomes. We systematically studied pair-wise antibiotic interactions in thre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…To examine BLM/MEM combination in a more clinically relevant setting, the checkerboard assays were repeated against the 9 CRE strains in M9 broth supplemented with 0.4% glucose, which has been reported to mimic the lung environment. [54] We found that BLM/MEM retains its antibacterial activity and strong synergistic interactions against all tested pathogens in M9 media (Figure S7, Supporting Information).…”
Section: Synergy Analysis and Activity Spectra Profiling Of Blm/mem A...mentioning
confidence: 87%
“…To examine BLM/MEM combination in a more clinically relevant setting, the checkerboard assays were repeated against the 9 CRE strains in M9 broth supplemented with 0.4% glucose, which has been reported to mimic the lung environment. [54] We found that BLM/MEM retains its antibacterial activity and strong synergistic interactions against all tested pathogens in M9 media (Figure S7, Supporting Information).…”
Section: Synergy Analysis and Activity Spectra Profiling Of Blm/mem A...mentioning
confidence: 87%
“…Additionally, synergistic or antagonistic interactions between different antibiotics depend on the composition of the environment. Understanding these interactions in vivo can inform the selection of combination therapies for difficult‐to‐treat infections (Davis et al., 2024).…”
Section: In Vivo Activity Of Antibioticsmentioning
confidence: 99%
“…Only a few studies have explored interspecific variation of DDI scores (Spitzer et al 2011; Robbins et al 2015; Brochado et al 2018; Davis et al 2022), but they have demonstrated that DC experiments (used to obtain DDI scores) could be scalable in the number of species and strains. A high throughput study of DDIs in gram-negative bacteria has shown that synergies are more conserved across species than antagonisms and additive combinations (Brochado et al 2018).…”
Section: Introductionmentioning
confidence: 99%